2012
DOI: 10.1088/0004-637x/746/2/151
|View full text |Cite
|
Sign up to set email alerts
|

The 2010 VERY HIGH ENERGY Γ-Ray FLARE AND 10 YEARS OF MULTI-WAVELENGTH OBSERVATIONS OF M 87

Abstract: The giant radio galaxy M 87 with its proximity (16 Mpc), famous jet, and very massive black hole ((3−6)×10 9 M ) provides a unique opportunity to investigate the origin of very high energy (VHE; E > 100 GeV) γ -ray emission generated in relativistic outflows and the surroundings of supermassive black holes. M 87 has been established as a VHE γ -ray emitter since 2006. The VHE γ -ray emission displays strong variability on timescales as short as a day. In this paper, results from a joint VHE monitoring campaign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
146
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 94 publications
6
146
0
Order By: Relevance
“…Observations of fast variability for a number of blazars have already been reported in the literature (Aharonian et al 2007;Albert et al 2007;Abramowski et al 2010Abramowski et al , 2012Acciari et al 2010Acciari et al , 2008Arlen et al 2013). As there is no unique way of measuring the variability, the time scales reported in the literature are often derived in different manners and have to be put into the same scale.…”
Section: Data Selection and Analysismentioning
confidence: 85%
“…Observations of fast variability for a number of blazars have already been reported in the literature (Aharonian et al 2007;Albert et al 2007;Abramowski et al 2010Abramowski et al , 2012Acciari et al 2010Acciari et al , 2008Arlen et al 2013). As there is no unique way of measuring the variability, the time scales reported in the literature are often derived in different manners and have to be put into the same scale.…”
Section: Data Selection and Analysismentioning
confidence: 85%
“…Narayan & Piran (2012) considered a turbulent process, modelled by a random motion of minijets inside the jet. Models involving minijets have also been invoked to explain the fast variations in the emission of radio galaxies (Giannios et al 2010), though the time scales of variations observed at VHE are much longer than for blazars, approximately a day for M 87 (Abramowski et al 2012). A&A 548, A123 (2012) These models are additive (the flux is given by the sum of the contributions of several regions) and, provided there are finite moments for the individual components, the central limit theorem (CLT) can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…[18] and triggered an extensive multiwavelength campaign at lower energies. Figure 5b shows results from the coordinated observation with VERITAS, H.E.S.S., and MAGIC during the bright VHE flare in 2010 [15]. This TeV flare was very well sampled, and the light curve shows a single isolated flare characterized by two-sided exponential decay τ rise ∼ 1.7 days and τ decay ∼ 0.6 days.…”
Section: Extragalactic Tev Gamma-ray Sources Detected By Veritasmentioning
confidence: 99%
“…The source has exhibited three distinct VHE flares with similarities in the VHE behaviour, but no unique multi-wavelength correlation. Figure 5a shows the multiwavelength light curves of M 87 over ten years of observations [15]. The exact location of the VHE gamma-rayemitting region in M 87 remains elusive.…”
Section: Extragalactic Tev Gamma-ray Sources Detected By Veritasmentioning
confidence: 99%